METODOLOGI DISIPLIN OCCIDENTALISME ALTERNATIF: TUMPUAN KHUSUS TERHADAP PANDANGAN ORIENTALIS TERHADAP HUKUM ISLAM: Alternative Occidentalisme Disciplanary Methodology: A Special Focus on Orientalist Views of Islamic Law - Abd Rahim, Rahimin Affandi (Jurnal Syariah, 2011)
Since modern times, the discourse of Islam established by western orientalism hascreated a disturbing response among Muslim scholars. Due to the peaceful nature of Islam, which is strongly opposed to any harsh confrontation withothers, we suggest thatMuslim scholars should promote the discipline of occidentalism embodied with the Islamic point of view. Consequently, such suggested discipline can be used to renew the negative image imposed by orientalists upon the Muslim civilization. Based on this background, this article will analyse orientalism’s attitude towards Islamic law by utilizing the methodologies proposed by the Islamic discipline of occidentalism. In order to achieve such objectives, this article is divided into several sections, namely, first the basic premise that initiated the concept of the disciplineof Islamic occidentalism. In the second and third section, special investigation will be placed on the recent occidentalism studies and its mode of operation in discussing these proposed subjects. In the fourth section, we may scrutinize the orientalist’s premise concerning Islamic law by utilizing the proposed concept as well as the methodologies of the Islamic discipline of occidentalism. Finally, the study will be concluded with various suggestions.